A case of pleomorphic adenoma of the inferior turbinate - Sedat Aydın; Özlem Çelebi; Arif Şanlı; Ümit Hardal (Turkish Archives of Otorhinolaryngology, 2010)

(untitled)
Pleomorphic adenoma is the most frequent tumor of the major salivary glands. Although it has also been reported to be present in the neck, ear, mediastinum, external nose and nasal cavity. Intranasal localization of this lesion is very rare and mainly originates from the nasal septum. From wherever the lesion originates, the main treatment modality should be surgical. In this article, we present a 33 year-old woman with a 4- year history of left-sided nasal obstruction. Endoscopic examination of the left nasal cavity showed that the mass seemed to originate from left inferior turbinate and protrude to the left nasal cavity. Due to the expansile nature of the lesion, a left alar incision was performed. She was followed-up after surgery for 18 months. A careful review of the literature has revealed that this is a highly unusual site for such neoplasms. For this reason, we approved to present this case.